2021
DOI: 10.1186/s12876-021-02046-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different embolic particles for superior rectal arterial embolization of chronic hemorrhoidal bleeding: gelfoam versus microparticle

Abstract: Background Whether different embolic particles with comparable diameter lead to similar beneficial effects in endovascular embolization of hemorrhoidal disease remains to be established. We sought to evaluate the efficacy and safety of different types of agents for superior rectal arterial embolization (SRAE) in patients with bleeding hemorrhoids. Methods Patients with recurrent episodes of internal hemorrhoidal bleeding and chronic anemia treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The various SRA embolizing agents used in the studies demonstrated similar clinical efficacy with satisfactory results, and no significant complications such as ischemic necrosis were observed [2,30]. Coils have the advantage of precisely controllable embolization at the bleeding site.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The various SRA embolizing agents used in the studies demonstrated similar clinical efficacy with satisfactory results, and no significant complications such as ischemic necrosis were observed [2,30]. Coils have the advantage of precisely controllable embolization at the bleeding site.…”
Section: Discussionmentioning
confidence: 77%
“…Transmural branches of the SRA play a crucial role in the arterial blood supply of the CCR. In this regard, many researchers have applied a series of endovascular treatments based on the vascular nature and anatomy of hemorrhoids [2,8,21,22,24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations